Unexpectedly high catch-and-release rates in European marine recreational fisheries: implications for science and management - Ferter, Keno (2017)
While catch-and-release (C&R) is a well-known practice in several European freshwater recreational fisheries, studies on the magnitude and impact of this practice in Europeanmarine recreational fisheries are limited. To provide an overview of the practice andmagnitude of C&R among marine recreational anglers in Europe, the existing knowledge of C&R and its potential associated release mortality was collected andsummarized. The present study revealed that in several European countries over half of the total recreational catch is released by marine anglers. High release proportions of > 60% were found for Atlantic cod (Gadus morhua), European sea bass (Dicentrarchus labrax), pollack (Pollachius pollachius), and sea trout (Salmo trutta) in at least one of the studied European countries. In the case of the German recreational Baltic Sea cod fishery, release proportions varied considerably between years, presumably tracking a strong year class ofundersized fish. Reasons for release varied between countries and species, and included legal restrictions (e.g. minimumlanding sizes and daily bag limits) and voluntary C&R. Considering the magnitude of C&R practice among European marine recreational anglers, post-release mortalities of released fish may need to be accounted for in estimated fishingmortalities.However, as the survival rates of Europeanmarine species aremostly unknown, there is a need to conduct post-release survival studies and to identify factors affecting post-release survival. Such studies could also assist in developing species-specific, best-practice guidelines to minimize the impacts of C&R on released marine fish in Europe.